Understanding Turnover as a Lifecycle Process: The Case of Young Nurses - Côté, Nancy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
SummaryBased on the life course perspective and the sociology of individuation, this article aims to examine the temporal processes at work in the decision of nurses to leave their jobs and the role played by different life contexts in guiding this decision. A qualitative study was conducted with nurses in order to gain an in-depth understanding of the reasons why so many young nurses decide to leave their jobs.The theoretical perspective used focuses on the importance of considering the interaction between the different spheres of a person’s life, the social environment in which they live and the work-related decisions they make. We conducted life-narrative interviews during which the nurses were asked about their overall work trajectory and the events in their work, personal, family, and social lives which, in their opinion, contributed to their decision to leave their jobs. A total of 26 nurses under the age of 35 were interviewed. The data analysis helped to identify several job-leaving pathways structured around three main dimensions: 1- the temporal aspects of the job-leaving pathways (short or long term); 2- the nurses’ subjective work experience; and 3- the stage in the nurses’ work lives or personal lives in which they found themselves when they made the decision.The findings reveal that the nurses’ decision to leave their jobs represents a complex process that developed over a short or longer period of time and involved various dimensions of their lives. Our analysis brought out two sources of tension underlying the nurses’ decision to leave their jobs: 1- a gap between their expectations regarding the possibilities for self-realization in their jobs and the concrete realities of work; and 2- a job situation that limited the possibilities to self-realize in other spheres of their lives.